Post-Occupancy Evaluation of Facade Design and Performance in Terms of User Satisfaction for Architecture Office Building, EMU - Sürme, Ömer Anıl (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The building construction industry is developing significantly and the development is decreasing the design and construction time. The necessity of achieving user satisfaction and feedbacks became more important compared to history. One of the most important parts of the building is a facade. The design and performance of the facade have an important effect to achieve user satisfaction at an indoor environment. Facade can play a big role in balancing different aspects of indoor environment quality such as view to outdoor, privacy level, air quality, thermal comfort, and natural lighting. Facades that designed according to contextual features can promise for achieving high satisfaction and comfort for building occupants. Consequently, it is important to take into account in designing facade and developing according to occupant’s needs. In order to understand the user satisfaction and collect feedbacks, post-occupancy evaluation (POE) method is developed. It is an essential method to evaluate the design success of the building and the performance after an occupancy. The different type of POE is applied to several buildings to examine various parts of the building in terms of user satisfaction but there are few numbers of POE that applied to examine facade design and performance for user satisfaction. This study focused on evaluation of facade design and performance of the selected office building by POE. The indicative POE method applied with questionnaire and observations of users and author. The study evaluated the facade of Architecture Office Building in EMU Campus, Famagusta, North Cyprus. The results were discussed and possible solutions for the case and recommendations for future projects are provided. Keywords: Office Building, Facade Design, Facade Performance, User Satisfaction, Post Occupancy Evaluation.

ÖZ: Yapı inşaat sektörü önemli ölçüde gelişiyor ve bu gelişmeler, tasarım ve yapım süresini kısaltıyor. Kullanıcı memnuniyeti ve geri bildirimleri elde etmenin gerekliliği, geçmişe oranla daha önemli hale geldi. Yapının en önemli bölümlerinden biri cephedir. Cephe tasarımı ve performansı, iç mekanlarda kullanıcı memnuniyetini sağlamakta büyük bir role sahiptir. Dış cephe; gizlilik seviyesi, hava kalitesi, termal konfor ve doğal aydınlatma gibi iç mekan çevre kalitesinin farklı yönlerini dengelemede büyük bir role sahiptir. Çevresel faktörlerin göz önüne alınması ile tasarlanan cepheler, bina kullanıcıları için yüksek memnuniyet ve rahatlık sağlamak için umut verebilir. Sonuç olarak, cephe tasarım süreci, kullanıcı memnuniyeti ve ihtiyacını dikkate alarak tasarlanmalı ve inşa edilmelidir. Kullanıcı memnuniyetini anlamak ve geri bildirim toplamak için, kullanım sonrası değerlendirme (KSD) yöntemi geliştirilmiştir. Binanın tasarım başarısını ve kullanım sonrası performansı değerlendirmek için önemli bir yöntemdir. Binanın çeşitli kısımlarını kullanıcı memnuniyeti açısından incelemek için, çeşitli binalara farklı KSD türleri uygulanmıştır, fakat kullanıcı memnuniyeti icin cephe tasarımı ve performansı ile ilgili uygulanan az sayıda KSD örneği vardır. Bu çalışma, seçilen ofis binasının cephe tasarımını ve performansını Belirleyici Düzeyde KSD yöntemi ile değerlendirmeye odaklanmıştır. Kullanıcı anketi ve gözlem yöntemleri ile bilgiler toplanmıştır. Çalışma, , DAÜ Kampüsü, Gazimağusa, Kuzey Kıbrıs'ta yer alan Mimarlik Fakültesi Ofis Binası’nı ele almıştır. Sonuçlar değerlendirilip, bina için olası çözümler ve gelecekteki projeler için öneriler sağlanmıştır. Anahtar Kelimeler: Ofis Binası, Cephe Tasarımı, Cephe Performansı, Kullanıcı Memnuniyeti, Kullanım Sonrası Değerlendirme.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2019. Supervisor: Assoc. Prof. Dr. Müjdem Vural.
Keywords: Architecture; Facades--Architectural Design--Eastern Mediterranean University; Office Building; Facade Design; Facade Performance; User Satisfaction; Post Occupancy Evaluation